INTERNATIONAL JURISDICTION OF SERBIAN COURTS AND COPYRIGHT INFRINGEMENT OVER THE INTERNET: AN INTERPRETATION OF ARTICLE 53 PARAGRAPH 1 OF THE SERBIAN PIL CODE - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The nature of the internet as a means of communication and information exchange gives rise to specific problems in private international law. One of them refers to the determination of international jurisdiction in cases of violation of economic and moral rights of authors committed through the use of the internet. In the context of Serbian law and in connection with this type of disputes, domestic courts have an opportunity to provide an answer to the question of how to interpret the provision of Article 53 paragraph 1 of the Serbian PIL Code, which establishes jurisdiction of Serbian courts for disputes arising from non-contractual liability in cases in which the damage occurred on the territory of Serbia. The paper argues that, in these type of disputes, it is inappropriate to equate the place where the damage occurred with the place from which it is possible to access the protected content. Instead, the existence of a strong connection between the dispute and Serbia and the protection of the interests of both parties in the proceedings are better protected by the acceptance of jurisdiction in a situation where it is possible to conclude that the actions of an alleged infringer were directed towards internet users on the territory of Serbia.
Keywords: international jurisdiction, copyright, the internet, the place where the damage occurred